Select overexpression of homer1a in dorsal hippocampus impairs spatial working memory - Celikel, Tansu; Marx, Verena; Freudenberg, Florian; Zivkovic, Aleksander; Resnik, Evgeny; Hasan, Mazahir T.; Licznerski, Pawel; Osten, Pavel; Rozov, Andrej; Seeburg, Peter H.; Schwarz, Martin K. (Frontiers in Neuroscience, 2007)
Long Homer proteins forge assemblies of signaling components involved in glutamate receptor signaling in postsynaptic excitatory neurons, including those underlying synaptic transmission and plasticity. The short immediate-early gene (IEG) Homer1a can dynamically uncouple these physical associations by functional competition with long Homer isoforms. To examine the consequences of Homer1amediated "uncoupling" for synaptic plasticity and behavior, we generated forebrain-specific tetracycline (tet) controlled expression of Venus-tagged Homer1a (H1aV) in mice. We report that sustained overexpression of H1aV impaired spatial working but not reference memory. Most notably, a similar impairment was observed when H1aV expression was restricted to the dorsal hippocampus (HP), which identifies this structure as the principal cortical area for spatial working memory. Interestingly, H1aV overexpression also abolished maintenance of CA3-CA1 long-term potentiation (LTP). These impairments, generated by sustained high Homer1a levels, identify a requirement for long Homer forms in synaptic plasticity and temporal encoding of spatial memory.